Assessment of the Application of Content and Language Integrated Learning in a Multilingual Classroom - Tatiana Baranova; Dmitriy Mokhorov; Aleksandra Kobicheva; Elena Tokareva (MDPI AG, 2021)
(1) Background: based on the constantly increasing requirements for modern university graduates, we have developed an educational model that allows us to introduce content and language integrated learning into classes with a multilingual approach, which will allow students to use several foreign languages in the process of professional communication. The purpose of the paper is to evaluate the efficiency of a newly introduced integrated learning model from the perspective of students, to identify the impact of such a model on students' professional discipline learning outcomes and to determine if the learning model contributes to an improvement in foreign language proficiency. (2) Methods: for our research we used qualitative and quantitative data from students' records of professional discipline and Spanish testing, as well as surveys and interviews on proposed learning model efficiency. Two groups of students took part in the experiment (N = 23 and N = 24). (3) Results: results on students' Spanish proficiency showed that the proposed learning model had a positive influence. Students from the experimental group got higher results on Listening, Reading and Speaking. According to results on professional discipline, both groups achieved approximately equal scores. Moreover, students described such a proposed learning model as efficient and progressive, giving a lot of advantages. (4) Conclusions: the experiment conducted confirmed the efficiency of the proposed learning model. In conclusion, it can be recommended for the realization of a multilingual approach, as well as the learning of a professional discipline.